1998
DOI: 10.1007/s004310050824
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of febrile seizures in siblings: a practical approach

Abstract: The cumulative risk of FS in siblings of children with FS is increased. The age attained risk of FS can be estimated using a practical model incorporating three readily available risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Despite the common belief that the rise in temperature per se is more important for the development of FS than the actual temperature achieved, there is no evidence to support that view [14,55]. Fever in children with FS is typically higher than in controls with similar fever-related illnesses, and seizures usually develop in the first 24 hours of the illness [91]. Measurements of fever have methodological problems because some reports in the literature refer to axillary temperature and some to rectal temperature, and because FS does not always occur at the peak level of fever or at the onset of fever [91].…”
Section: Fevermentioning
confidence: 84%
See 2 more Smart Citations
“…Despite the common belief that the rise in temperature per se is more important for the development of FS than the actual temperature achieved, there is no evidence to support that view [14,55]. Fever in children with FS is typically higher than in controls with similar fever-related illnesses, and seizures usually develop in the first 24 hours of the illness [91]. Measurements of fever have methodological problems because some reports in the literature refer to axillary temperature and some to rectal temperature, and because FS does not always occur at the peak level of fever or at the onset of fever [91].…”
Section: Fevermentioning
confidence: 84%
“…Fever in children with FS is typically higher than in controls with similar fever-related illnesses, and seizures usually develop in the first 24 hours of the illness [91]. Measurements of fever have methodological problems because some reports in the literature refer to axillary temperature and some to rectal temperature, and because FS does not always occur at the peak level of fever or at the onset of fever [91]. Although the average level of fever in children with FS is high (39.8°C), the seizure itself is the first sign of febrile illness in 25-50% of all cases of FS [30].…”
Section: Fevermentioning
confidence: 98%
See 1 more Smart Citation
“…In cohorts of children with FS, the risk that siblings will have an FS is 10-45%. 27 Many studies have also found that the risk may be increased by an underlying brain disorder. Premature birth, delayed discharge from the neonatal intensive care unit, and developmental delay are potential markers for suboptimal brain function, but there is conflicting evidence definitively linking these factors and FS, 16 21 24 28-31 which may in part reflect whether the study was hospital or community based.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The most commonly defined risk factor is family history in first degree family members. Cohort studies in patients with febrile convulsion; risk of siblings was determined as 10-45% (11). Cognitive dysfunction, psychomotor retardation, behavioral problems, pica, breath holding spells, restless leg syndrome, and thrombosis could be associated with iron deficiency.…”
Section: Introductionmentioning
confidence: 99%